Accounting knowledge, quantification, and budget effects on the sunk cost fallacy. - Ang, Geok Lan (2014)
In this study, we investigate the factors that may reduce the sunk cost fallacy. Based on the results of experiments conducted with undergraduates in NTU & NUS, we concluded that the sunk cost effect can be reduced: